Reductive intramolecular cyclisation of unsaturated halides by Ni(II) complexes - Esteves, Ana Paula (2001)
Catalytic reductions of 6-bromo-1-hexene and (R)-(-)-citronellyl bromide with Ni(I) complexes, electrogenerated from Ni(II) complexes, in N,N%-dimethylformamide have been investigated with the aid of cyclic voltammetry and controlled-potential electrolyses. Cyclic compounds are obtained in appropriate experimental conditions. The influence of a proton donor and a hydrogen atom donor on the system is described.